The wrinkling concept applied to plasma‐deposited polymer‐like thin films: A promising method for the fabrication of flexible electrodes. Issue 9 (23rd July 2020) - Thiry, Damien; Vinx, Nathan; Damman, Pascal; Aparicio, Francisco J.; Tessier, Pierre‐Yves; Moerman, David; Leclère, Philippe; Godfroid, Thomas; Desprez, Sylvain; Snyders, Rony
Abstract: In this communication, we report on an innovative solvent‐free method that allows for the design of nano‐/micropatterns with tuneable dimensions. Our approach is based on the spontaneous wrinkling phenomenon taking place in a bilayer system formed by a mechanically responsive bottom plasma polymer layer and a top aluminum thin film. The dimensions of the wrinkles can be adjusted in a wide range (i.e., from nanometer to micrometer range) by modulating the cross‐linking density as well as the thickness of the plasma polymer layer. Finally, it is demonstrated that these wrinkled surfaces could efficiently be used as flexible electrodes. The whole set of our data unambiguously reveals the attractiveness of our method for the fabrication of the micro‐/nanopattern with dimensions on demand. Abstract : A versatile and innovative strategy is developed for the fabrication of a micro‐/nanopattern with dimensions on demand based on the wrinkling concept applied to plasma polymers. Our strategy includes the generation of surface instabilities in a bilayer system formed by a mechanically responsive plasma polymer and top aluminum thin film.